2018
DOI: 10.5194/hess-2018-85
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Probability Distribution of Daily Precipitation at the Point and Catchment Scales in the United States

Abstract: Abstract. Choosing a probability distribution to represent daily precipitation depths is important for precipitation frequency analysis, stochastic precipitation modeling and in climate trend assessments. Early studies identified the 2-parameter Gamma (G2) distribution as a suitable distribution for wet-day precipitation based on traditional goodness of fit tests. Here, probability plot correlation coefficients and L-moment diagrams are used to examine distributional alternatives for the full-record and wet-da… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Logistic distribution is a continuous probability distribution. It defined by two parameters for all the real numbers, which are a scale s and a location μ (Ye et al, 2018). Its PDF plot is always symmetric about the mean.…”
Section: Methodsmentioning
confidence: 99%
“…Logistic distribution is a continuous probability distribution. It defined by two parameters for all the real numbers, which are a scale s and a location μ (Ye et al, 2018). Its PDF plot is always symmetric about the mean.…”
Section: Methodsmentioning
confidence: 99%
“…Three distributions are chosen which are gamma, Log-Normal and Generalized Pareto distributions (GPD) are tested on multivariate rainfall data. These distributions are commonly used as potential candidates for the data generating mechanism of rainfall data [20][21][22]. Estimation of the parameters for each of the above sampled probability distributions are based on the summary statistics from the daily torrential rainfall data in Peninsular Malaysia.…”
Section: Simulation Procedures For Generating Synthetic Rainfall Datamentioning
confidence: 99%
“…On the basis of the results, the mixed exponential distribution showed the best fit for the data followed by the gamma and exponential distributions, respectively. Ye, Hanson, Ding, Wang, and Vogel (2018) evaluated the performance of 15 distributions in 237 rainfall gauge stations in the United States. The results indicated that the four‐parameter kappa distribution showed the best performance to describe the occurrence of daily rainfall in the rainfall gauge stations.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, assessing the applicability of CDFs with different structures is necessary to provide more accurate information on rainfall. In practice, precipitation is simulated using the gamma distribution that in most cases is able to adequately estimate low and moderate rainfall due to its flexibility (Kist & Virgens Filho, 2015; Papalexiou, Koutsoyiannis, & Makropoulos, 2013; Ye et al, 2018; Yoo, Jung, & Kim, 2005). However, the gamma distribution may not be adequate in cases of extreme precipitation values, as magnitude and frequency are often underestimated (Allard & Bourotte, 2015; Kleiber, Katz, & Rajagopalan, 2012).…”
Section: Introductionmentioning
confidence: 99%